Specific formation of middle class during the period of kazakhstan’s modernization - Nuran, D. N.; Bolysbaeva, S. M. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2013)
The article considers the middle class as the main guarantor of formation of the social state and its specific formation in modern Kazakhstan. Kazakhstan as the democratic, secular, constitutional and social state, on the first place puts life, the rights and freedoms of the people. Our main strategies of development of the country «Social modernization of Kazakhstan: Twenty steps to Society of General Work», “Strategy Kazakhstan-2050”: new political course of the established state” and etc. aim over creation social the state, that is middle class. After a rupture of the Soviet Union, the Republic of Kazakhstan occurred in the conditions of an economic crisis, the middle class which existed before generally stopped existence. In the countries with the developed market structure the middle class represents overwhelming part of social structure of society and acts as the guarantor of its stability. Stability of social structure of society in a considerable measure depends on the specific weight and a center or «middle class» role. The more quantitatively the middle class, the more it influences state policy, process of formation of fundamental values of society, promoting socio-political stability and forward economic development. The weakening of middle class happening in the period of economic crises, leads society to serious social shocks. In this aspect the substantial social and economic policy directed on support of basic layers of middle class, first of all representatives of small and medium business for the purpose of prevention of their marginalization is important.The main condition of increase of a role of middle class - development of national economy, socially oriented market economy. The state seeks to support this new social group, in particular such measures, as introduction of the moratorium on checks of small and medium business from supervisory authorities which work during the certain periods connected with the general unfortunate world economic trends. Social activity of middle class becomes a condition of formation of civil society, and small number, not formation of middle class conduct to political instability. The middle class forms a certain economic niche, the mental environment of society which is characterized by special type of professionalism and civil culture of participation, that is a necessary component of a sustainable development of democratic society.